Polyhydroxyalkanoate recovery - Hassan, Mohd Ali; Mohammadi, Mitra; Phang, Lai Yee; Ariffin, Hidayah; Yee, Lian Ngit; Shirai, Yoshihito (2012)
An environment friendly, simple and energy efficient process for recovery of polyhydroxyalkanoate (PHA) from biomass materials at a useful level of quality and purity is accomplished by employing an environmental-friendly halogen-free method for polyhydroxyalkanoate (PHA) recovery selectively from wet biomass materials and involving freezing and thawing.